Detection of human papillomavirus in dental biofilm and the uterine cervix of a pregnant adolescent - Cavalcanti, Édila Figuerêdo Feitosa (2016)
CONTEXT: Adolescence and pregnancy are considered to be risk factors for human papillomavirus (HPV) infection. The relationship between this infection in the uterine cervix and oral HPV infection is controversial. CASE REPORT: This report describes a case of a pregnant 16-year-old adolescent who presented HPV infection in the uterine cervix and the mouth. Smears were collected from the cervix and the tongue/ palate. Dental biofilm samples were also collected. The microarray technique was used to detect HPV. The HPV 56 subtype was observed in the cervical smear and HPV 6 in dental biofilm. CONCLUSION: In this pregnant adolescent, HPV infection was present in both the cervix and the mouth, but the HPV subtypes infecting these two areas were different.